2011
DOI: 10.3233/ip-2011-0220
|View full text |Cite
|
Sign up to set email alerts
|

Whose e-democracy? The democratic divide in American electoral campaigns

Abstract: This study examines whether a democratic divide (a gap in political participation via the Internet) exists among demographic segments during the campaign season of the 2008 U.S. presidential election. Five different types of online political activity are compared in terms of the divide pattern: conversation, mobilization, information consumption, information production, and activity on social networking sites. Demographic and socioeconomic characteristics such as age, gender, race, education and income are det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Participants ( n = 419) were students attending McGill University, located in Montreal, Quebec, Canada, during the 2011 winter term. This sample was chosen in order to avoid floor effects in the dependent variable, as young people may be more likely to engage in online political participation than older people (Nam, 2011). Political interest of participants was assessed to determine whether the sampling technique recruited a greater proportion of people who were interested in politics.…”
Section: Methodsmentioning
confidence: 99%
“…Participants ( n = 419) were students attending McGill University, located in Montreal, Quebec, Canada, during the 2011 winter term. This sample was chosen in order to avoid floor effects in the dependent variable, as young people may be more likely to engage in online political participation than older people (Nam, 2011). Political interest of participants was assessed to determine whether the sampling technique recruited a greater proportion of people who were interested in politics.…”
Section: Methodsmentioning
confidence: 99%
“…A government media scheme that depends heavily on Twitter can discriminate against those who do not use social media. This can become a critical problem about the information and democratic divide when non-Twitter using citizens do not receive enough information from a government which uses Twitter as its primary mode of communication (Nam 2011). Twitter use can also yield communication problems resulting from the over-representation of minority opinions, as it can mainly reflect heavy users' and advocates' ideas (Kim, Park, and Rho 2015).…”
Section: Practical Highlights: Prudent Leading Officers' Utilization mentioning
confidence: 99%
“…One significant difference, though, is that it casts doubts on how individuals' experience of computers really is linked to the dependent variable. Since this model does not report significant results regarding this variable, the fourth hypothesis can be questioned as well as how findings from previous noteworthy research [4,39] are reflected in a Swedish context. Statistical tests concerning these models verify that the estimations are of importance.…”
Section: Explaining Variation In Demand For E-democracymentioning
confidence: 83%
“…The fourth hypothesis is operationalized through a question concerning self-estimation of knowledge of computers. As noted earlier, several scholars [4,12,21,39] underline how internet skills or experience are related to e-democracy. Regarding the fifth hypothesis, resource theory [59] states that access to certain resources stimulates political participation, and scholars [4,41] have shown that this statement can be expanded to include the online environment.…”
Section: Methodology and Datamentioning
confidence: 96%
See 1 more Smart Citation